Causes and circumstances of accidents at work in the European Union, Slovakia and Czech Republic - Hollá, Katarína; Ďad'ová, Alena; Hudáková, Mária; Valla, Jirí; Cidlinová, Anna; Osvaldová, Linda Makovická (Frontiers in Public Health, 2023)
There are several challenges in occupational safety and health that need to be addressed. The basic premise is the reduction of occupational accidents in individual sectors. Finding effective tools to reduce them is very challenging. Safety culture is perceived differently in the countries of the European Union. The Slovak Republic and the Czech Republic became members in the same year, the historical development is roughly the same. The basic intention of this article is to compare the accident rate in these two countries and in the European Union. This comparison is based on the statistical processing of data by NACE category and representation of accident rates in individual industries. In the end, the main causes of accidents were identified, which gives space for further research in this field.